Wuluh fruitstar extract effect with different amounts of quality freshness of the fish tambakan (helostoma temmincki) - Oktori, Ranggi; Buchari, Dewita; ', Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The purpose of this study was to determine the quality of fish tambakan setback at room temperature which has been soaked in the wuluh fruitstar, reviewed in TVB and TPC, pH and organoleptic. Fish tambakan (Helostoma temmincki) with a size of Â± 10-15 cm / tail obtained from the market in a reed hut. Fish was appointed to the laboratory alive, surviving fish tambakan left to die, then once dead fish, fish washed up mucus attached wasted and undrained for 15 minutes, then fish soaked in a solution of starfruit fruit extracts with level factor (K0) 0 ml, (K1) 100 ml, (K2) 200 ml, (K3) 300 ml for 15 min and stored at room temperature in accordance with group 0 hour (H1), 3 hours (H2), 6 hours (H3), 9 hours (H4) and 12 hours (H5). The parameters used are TVB analysis, total plate count (TPC), pH and organoleptic analysis appearance.Keywords: fish tambakan, wuluh fruitstar ekstract